When Do Creditor Rights Work? - Safavian, Mehnaz; Sharma, Siddharth (World Bank, Washington, DC, 2012)
Creditor-friendly laws are generally associated with more credit to the private sector and deeper financial markets. But laws mean little if they are not upheld in the courts. The authors hypothesize that the effectiveness of creditor rights is strongly linked to the efficiency of contract enforcement. This hypothesis is tested using firm level data on 27 European countries in 2002 and 2005. The analysis finds that firms have more access to bank credit in countries with better creditor rights, but the association between creditor rights and bank credit is much weaker in countries with inefficient courts. Exploiting the panel dimension of the data and the fact that creditor rights change over time, the authors show that the effect of a change in creditor rights on change in bank credit increases with court enforcement. In particular, a unit increase in the creditor rights index will increase the share of bank loans in firm investment by 27 percent in a country at the 10th percentile of the enforcement time distribution (Lithuania). However, the increase will be only 7 percent in a country at the 80th percentile of this distribution (Kyrgyzstan). Legal protections of creditors and efficient courts are strong complements.